2009
DOI: 10.1258/ijsa.2008.008211
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of asymptomatic rectal Chlamydia trachomatis: is single-dose azithromycin effective?

Abstract: Rectal infection with Chlamydia trachomatis affects approximately 7% of men having sex with men (MSM), attending departments of Genito-Urinary (GU) Medicine [Manavi et al. Int J STD AIDS 2004;15:162-4], and the British Association for Sexual Health and HIV (BASHH) guidelines for the treatment of uncomplicated genital C. trachomatis infection include 1 g of single-dose oral azithromycin as a recommended regimen [BASHH 2006]. A retrospective analysis was performed on case-notes from all patients diagnosed with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 7 publications
1
44
2
Order By: Relevance
“…7,8,10 Emerging data suggest increased failure rates with oral azithromycin compared to doxycycline when used for the treatment of rectal CT infections. [24][25][26][27] Suboptimal treatment efficacy with azithromycin against rectal infections could have important implications for women who may be infected with CT at both urogenital and rectal sites, especially if the latter go unrecognized due to absent testing. If treated with azithromycin, these women could potentially have successful clearance of the urogenital infection, but not necessarily the rectal infection.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10 Emerging data suggest increased failure rates with oral azithromycin compared to doxycycline when used for the treatment of rectal CT infections. [24][25][26][27] Suboptimal treatment efficacy with azithromycin against rectal infections could have important implications for women who may be infected with CT at both urogenital and rectal sites, especially if the latter go unrecognized due to absent testing. If treated with azithromycin, these women could potentially have successful clearance of the urogenital infection, but not necessarily the rectal infection.…”
Section: Discussionmentioning
confidence: 99%
“…In MSM, a recent study in the USA found a 13% treatment failure rate for anal chlamydia infections treated with azithromycin. 16 Even if patients are reminded about the need for re-testing by their clinician, patients may not consider themselves at risk or perceive testing as a priority, and thus there will be considerable variation in patient adherence to this recommendation. Studies have examined various strategies for increasing return for retesting after a chlamydia infection, including cash incentives, phone and letter reminders, motivational counselling, a brief recommendation by the clinician and sending urine samples in the mail.…”
Section: Discussionmentioning
confidence: 99%
“…Drummond et al (55) reported that 6% of men treated for chlamydial rectal infections had apparent treatment failure, while a study by Hathorn and coworkers reported that 11 of 45 (21.4%) participants (male and females) treated for rectal infection and not at risk for reinfection had apparent treatment failure (56). Yet another study reported a 13% treatment failure rate in men with rectal infections (57). Interestingly, in the Hathorn study, the treatment failure with doxycycline was less frequent in the treatment of rectal infections (56).…”
Section: Implications Of Chlamydial Gi Infection For Persistent or Rementioning
confidence: 99%